Russian–Japanese Relations at the Turn of the Century: Patterns, Routes, Leaders - O. G. Paramonov (Международная аналитика)
This article analyzes why, during the post-Cold War period, Tokyo became aware of the need to reconsider its hard-line relations with Moscow, which had been developed in previous decades. Even in the period preceding the collapse of the USSR, Tokyo did not conceal its intentions to use the diﬃcult socio-economic situation in the USSR and then in Russia to obtain territorial concessions. Even then, however, the Russian side mostly determined the agenda of the Russian-Japanese dialogue, which was largely due to serious mistakes made by Japanese politicians. After Russia emerged from the economic and political turbulence that began unexpectedly for the West and Japan in the 2000s, Tokyo’s new hopes were connected with concessions on the “territorial case” because of Russia’s interest in Japanese investments and technological cooperation, especially for the development of the Far East and adjacent areas. Nevertheless, even here Tokyo faced a ﬁasco. Before the arrival of the Abe era in late 2012, Japan’s foreign policy toward Russia became increasingly “reactive,” and even later Tokyo’s high-proﬁle initiatives related to the Russian-Japanese agenda often turned out to be old proposals from Moscow that had been made during the time of Michael Gorbachev, and favorable moments for their implementation were largely missed.